Quality of malunggay (Moringa oleifera) crackers packed in low-density polyethylene (LDPE) and polypropylene (PP) during storage. - Cañete, Ma. Pauline Emmanuelle (2017.)
The study evaluated the suitability of two packaging materials, low-density polyethylene (LDPE) and polypropylene (PP), for extending the shelf-life of malunggay crackers. Changes in the physico-chemical (moisture content, water activity, and peroxide value [PV]), microbiologicaln(yeasts and molds count) and sensorial properties (general acceptability and attributes) of malunggay crackers packed in LDPE and PP and stored at room conditions (27°C - 30°C0 were monitored at regular intervals (7days) for 49 days. The moisture content, water activity and peroxide value of the malunggay crackers packed in LDPE and PP increased with storage time. The rate of increase was faster in the malunggay crackers packed in LDPE than those packed in PP. There was a significant difference on the moisture content, water activity and peroxide value of the malunggay crackers packed in LDPE and in PP during storage (Two-way ANOVA, α= 0.01). The yeast and molds count of the malunggay crackers packed in LDPE and PP increased with storage time. The yeast and mold growth which was lower in the malunggay crackers packed in PP all throughout the storage period differed from those packed in LDPE. There was a significant difference on the yeast and molds count of the malunggay crackers during storage time (Two-way ANOVA, α= 0.01). The appearance, color, saltiness, flavor and odor of the malunggay crackers packed in LDPE and PP had no significant difference during storage time (Kruskal Wallis at 5% level of significance). However, the texture and acceptability rating of the malunggay crackers packed in LDPE and PP significantly differed during storage. PP was shown to be better packaging material than LDPE for malunggay crackers.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Malunggay; Malunggay crackers; Moringa oleifera